(untitled) (Research, Society and Development, 2022)
Cassava has a wide genetic diversity, being largely cultivated by family farmers. The present study aimed to characterize by phenotype the landraces cultivated by family farmers in rural settlements in the State of Mato Grosso, Brazil. The study was carried out in three settlements, Nossa Senhora Aparecida (NSA) and Júlio Firmino Domingos (JFD) in the municipality of Alta Floresta and the São Pedro (ASP) settlement in Paranaíta. The landraces cultivated on the properties were surveyed and characterized, using 13 qualitative descriptors. The frequency of cultivation of landraces and the frequency of the phenotypic classes of each descriptor was calculated. To characterize the phenotypic diversity, the qualitative variables were analyzed as multicategorical multiple classes and grouped by the UPGMA method, using the Genes program. We visited 33 properties, and 76 landraces of cassava cultivated in the three settlements were identified. The “cacau” landrace was the most frequent, present in 69.7% of the properties, therefore it is the dominant landrace. The characterization presented a total of 44 phenotypic classes, evidencing phenotypic variability among the evaluated landraces. The UPGMA group formed nine groups, the GI group was the most representative (72.37%). The GVIII and GIX groups were composed of one landrace each, ASP59 (“roxa de fritar”) and JFD40 (“amarela”) respectively. Twenty-one landraces were identified, 15 of which were considered rare. The UPGMA carried out through the analysis of phenotypic characterization showed a wide diversity of landraces in the properties of the farmers, considered as maintaining units and conservation areas.